(untitled) (Bangladesh Journal of Medical Science, 2021)
Paederus dermatitis is a very painful vesicular condition which is caused by the extremely potent toxin “Pederin” released from an insect calledPaederusfuscipes but commonly known as Charlie.A 26 years old woman presented with a sudden onset of neuralgia, arthralgia of left jaw, fever, nausea and fatigue with generalized pain radiating to the neck and lower jaw as well as itch-like sensation on their left arm associated with acute inflammation which began 24-48 hours prior. The patient refused to go to the hospital due to the current pandemic situation but instead updated us daily on her conditions with photographic changes of the arm until complete resolution of symptoms. This case report accounts for the daily sequential changes experienced by a patient after severe reaction to an exposure of pederin with photographs of the affected site. While the painful lesion and all systemic conditions resolved spontaneously over time, a scar was left to mark the unpleasant period. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.459-462